Robot-Assisted Total Mesorectal Excision Versus Laparoscopic Total Mesorectal Excision: A Retrospective Propensity Score–Matched Cohort Analysis in Experienced Centers. Issue 2 (February 2022) - Burghgraef, Thijs Adriaan; Crolla, Rogier M.P.H.; Verheijen, Paul M.; Fahim, Milad; van Geloven, Anna; Leijtens, Jeroen W.A.; Pronk, Apollo; Smits, Anke B.; Verdaasdonk, Emiel G.G.; Consten, Esther C.J.
Abstract : BACKGROUND: The superiority of robot-assisted over laparoscopic total mesorectal excision has not been proven. Most studies do not consider the learning curve while comparing the surgical technique. OBJECTIVE: This study aims to compare laparoscopic with robot-assisted total mesorectal excision performed by surgeons who completed the learning curve of the technique. DESIGN: This is a multicenter retrospective propensity score–matched analysis. SETTINGS: The study was performed in 2 large, dedicated robot-assisted hospitals and 5 large, dedicated laparoscopic hospitals. PATIENTS: Patients were included if they underwent a robot-assisted or laparoscopic total mesorectal excision for rectal cancer with curative intent at a dedicated center for the minimally invasive technique between January 1, 2015, and December 31, 2017. INTERVENTIONS: We compared robot-assisted with laparoscopic total mesorectal excision. MAIN OUTCOME MEASURES: The main outcome was conversion to laparotomy during surgery. Secondary outcomes were postoperative morbidity and positive circumferential resection margin. RESULTS: A total of 884 patients were included and, after matching, 315 patients per treatment group remained. Conversion was similar between laparoscopic and robot-assisted total mesorectal excision (4.4% vs 2.5% ( p = 0.20)). Positive circumferential resection margin was equal (3.2% vs 4.4% ( p = 0.41)). Overall morbidity was comparable as well, although a lower rate of wound infections was observed in the robot-assisted group (5.7% vs 1.9% ( p = 0.01)). More primary anastomoses were constructed in the robot-assisted group (50.8% vs 68.3% ( p < 0.001)). Finally, more open procedures were performed in dedicated laparoscopic centers, with an overrepresentation of cT4N+ tumors in this group. LIMITATIONS: This is a retrospective multicenter cohort; however, propensity score matching was applied to control for confounding by indication. CONCLUSIONS: Robot-assisted and laparoscopic total mesorectal excision are equally safe in terms of short-term outcomes. However, with the robot-assisted approach, more primary anastomoses were constructed, and a lower wound infection rate was observed. See Video Abstract at http://links.lww.com/DCR/B677 . ESCISIÓN MESORRECTAL TOTAL ASISTIDA POR ROBOT VERSUS ESCISIÓN MESORRECTAL TOTAL LAPAROSCÓPICA: UNA PUNTUACIÓN DE PROPENSIÓN RETROSPECTIVA ANÁLISIS DE COHORTES EMPAREJADAS EN CENTROS EXPERIMENTADOS ANTECEDENTES: No se ha demostrado la superioridad de la escisión mesorrectal total asistida por robot sobre la laparoscópica. La mayoría de los estudios no tienen en cuenta la curva de aprendizaje al comparar la técnica quirúrgica. OBJETIVO: Este estudio tiene como objetivo comparar la escisión mesorrectal total laparoscópica con la asistida por robot realizada por cirujanos que completaron la curva de aprendizaje de la técnica. DISEÑO: Este es un análisis multicéntrico retrospectivo emparejado por puntuación de propensión. AJUSTES: El estudio se realizó en dos grandes hospitales dedicados asistidos por robots y cinco grandes hospitales laparoscópicos dedicados. PACIENTES: Se incluyeron pacientes que se sometieron a escisión mesorrectal total asistida por robot o laparoscópica para cáncer de recto con intención curativa, en un centro dedicado a la técnica mínimamente invasiva entre el 1 de enero de 2015 y el 31 de diciembre de 2017. INTERVENCIONES: Comparamos la escisión mesorrectal total asistida por robot con la laparoscópica. PRINCIPALES MEDIDAS DE RESULTADO: El principal resultado fue la conversión a laparotomía durante la cirugía. Los resultados secundarios fueron la morbilidad posoperatoria y el margen circunferencial positivo. RESULTADOS: Se incluyó a un total de 884 pacientes y, después de emparejar, quedaron 315 pacientes por grupo de tratamiento. La conversión fue similar entre la escisión mesorrectal total laparoscópica y asistida por robot (4, 4% frente a 2, 5% [ p = 0, 20]). El margen de resección circunferencial positivo fue igual (3, 2% vs 4, 4% [ p = 0, 41]). La morbilidad general también fue comparable, aunque se observó una menor tasa de infecciones de heridas en el grupo asistido por robot (5, 7% frente a 1, 9% [ p = 0, 01]). Se construyeron más anastomosis primarias en el grupo asistido por robot (50, 8% frente a 68, 3% [ p < 0, 001]). Finalmente, se realizaron procedimientos más abiertos en centros laparoscópicos dedicados, con una sobrerrepresentación de tumores cT4N + en este grupo. LIMITACIONES: Ésta es una cohorte multicéntrica retrospectiva; sin embargo, se aplicó el emparejamiento por puntuación de propensión para controlar los factores de confusión por indicación. CONCLUSIONES: La escisión mesorrectal total asistida por robot y laparoscópica son igualmente seguras en términos de resultados a corto plazo. Sin embargo, con el abordaje asistido por robot, se construyeron más anastomosis primarias y se observó una menor tasa de infección de la herida. Consulte Video Resumen en http://links.lww.com/DCR/B677 . (Traducción—Dr. Gonzalo Hagerman ) Abstract : Supplemental Digital Content is available in the text.